2008
DOI: 10.1017/s0007485308006226
|View full text |Cite
|
Sign up to set email alerts
|

Introgression of a disrupted cadherin gene enables susceptibleHelicoverpa armigerato obtain resistance toBacillus thuringiensistoxin Cry1Ac

Abstract: A disrupted allele (r1) of a cadherin gene (Ha_BtR) is genetically associated with incompletely recessive resistance to Bacillus thuringiensis toxin Cry1Ac in a Cry1Ac-selected strain (GYBT) of Helicoverpa armigera. The r1 allele of Ha_BtR was introgressed into a susceptible SCD strain by crossing the GYBT strain to the SCD strain, followed by repeated backcrossing to the SCD strain and molecular marker assisted family selection. The introgressed strain (designated as SCD-r1, carrying homozygous r1 allele) obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
91
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(100 citation statements)
references
References 31 publications
(44 reference statements)
8
91
1
Order By: Relevance
“…From 10 isofemale lines that yielded five or more survivors in the F 2 screen, we generated 10 resistant strains for further analysis (Materials and Methods). Sequencing of the cadherin gene revealed that three of these resistant strains from Anyang in northern China (AY9, AY16, and AY27) had the recessive cadherin resistance allele r 1 that was previously identified and characterized from the laboratoryselected SCD-r1 strain (23).…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…From 10 isofemale lines that yielded five or more survivors in the F 2 screen, we generated 10 resistant strains for further analysis (Materials and Methods). Sequencing of the cadherin gene revealed that three of these resistant strains from Anyang in northern China (AY9, AY16, and AY27) had the recessive cadherin resistance allele r 1 that was previously identified and characterized from the laboratoryselected SCD-r1 strain (23).…”
Section: Resultsmentioning
confidence: 90%
“…The cadherin r 1 allele originally identified from a laboratory-selected strain derived from Gaoyang of northern China in 2001 (22,23,26) was the most common resistance allele detected in fieldselected populations from northern China. This allele accounted for the resistance detected in 38% (three of eight) of resistant strains from Anyang of northern China (Table 1), which is about 300 km southwest of Gaoyang.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used diet surface overlay bioassays to test second instars that had been starved for 4 h. 18 Toxins were diluted with PBS (0.01 M, pH 7.4). We put 900 μl of liquid artificial diet in each well of a 24-well plate.…”
Section: H Armigeramentioning
confidence: 99%
“…14,15 Disruption of Bt toxin binding to midgut receptors is the most common general mechanism of insect resistance. 9 Mutations in the genes encoding midgut cadherins that bind Cry1Ac are linked with resistance in at least three lepidopteran pests of cotton, [16][17][18] but such cadherin mutations are not the primary cause of many other cases of field-and laboratory-selected resistance. 9,19,20 Although some aspects of the mode of action of Bt toxins remain unresolved, extensive evidence shows that after Cry1A protoxins are ingested by larvae, they are solubilized in the gut and cleaved by mid-gut proteases such as trypsin to yield activated 60-kD monomeric toxins that bind with membrane-associated receptors.…”
mentioning
confidence: 99%